Queen Kampa of Opobo Kingdom in the Eastern Niger Delta: The Founder of Kampa Town 1881- 1900 - Edna Adagogo-Brown, Dame (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This paper examines selected contributions of Ibani women to the growth and development of Opobo kingdom. One of such women was Queen Kampa, one of the principal wives of King Jaja of Opobo, who was said to have led an expedition against the Ibuno people of Ibibio extraction in 1881. The paper adopts the use of oral tradition, oral history and secondary sources to achieve the full investigation. This paper reveals that after the expedition, Queen Kampa opted to stay back at Kampa which she purchased from Elile people in Eastern Obolo of Akwa Ibom State. According to oral tradition, she adopted four sons, Nwachukwu, Nkanta, Etewo and Ekwe and divided the village amongst them. Her leadership brought about major changes that are worth critical analysis and, by implications, the paper seeks to encourage women who had discovered their hidden talents, not to relent in their efforts to make their marks for posterity as Queen Kampa had done.